PENDAMPINGAN KEGIATAN LITERASI DI SD NEGERI 01 MENDAYUN: ANALISIS IMPLEMENTASI DAN DAMPAKNYA - Sugiarti, Sugiarti; Alwina, Ulul (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
This article examines the literacy assistance activities carried out at SD Negeri 01 Mendayun as an effort to improve students' reading and writing skills. The assistance is provided through various methods and strategies to facilitate effective and enjoyable learning. The research method used includes participatory observation, in-depth interviews with teachers and students, and document analysis. The results of the study indicate that the literacy assistance activities have made a significant contribution to increasing students' reading interest and writing abilities. This article also discusses the implications of the research findings for the development of literacy programs in elementary schools.